2011
DOI: 10.1002/bdm.677
|View full text |Cite
|
Sign up to set email alerts
|

Predicting domain‐specific risk taking with the HEXACO personality structure

Abstract: Although risk taking traditionally has been viewed as a unitary, stable individual difference variable, emerging evidence in behavioral decision-making research suggests that risk taking is a domain-specific construct. Utilizing a psychological risk-return framework that regresses risk taking on the perceived benefits and perceived riskiness of an activity (Weber & Milliman, 1997), this study examined the relations between risk attitude and broad personality dimensions using the new HEXACO personality framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
126
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 74 publications
19
126
1
1
Order By: Relevance
“…However, the opposite was the case as these individuals preferred the smaller gain that could be safely attained through cheating. These findings also further specify the conclusions of Weller and colleagues (Weller & Thulin, 2012;Weller & Tikir, 2011) who showed that individuals high in HonestyHumility are more risk-averse in gambling paradigms. As shown in the current experiment, this pattern may reverse once risky behavior is the option compatible with ''lead us not into temptation'' -in such situations, individuals high in Honesty-Humility will actually act in a more risk-seeking way than their counterparts low in Honesty-Humility.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…However, the opposite was the case as these individuals preferred the smaller gain that could be safely attained through cheating. These findings also further specify the conclusions of Weller and colleagues (Weller & Thulin, 2012;Weller & Tikir, 2011) who showed that individuals high in HonestyHumility are more risk-averse in gambling paradigms. As shown in the current experiment, this pattern may reverse once risky behavior is the option compatible with ''lead us not into temptation'' -in such situations, individuals high in Honesty-Humility will actually act in a more risk-seeking way than their counterparts low in Honesty-Humility.…”
Section: Resultssupporting
confidence: 85%
“…Specifically, Weller and colleagues (Weller & Thulin, 2012;Weller & Tikir, 2011) recently showed that individuals low in Honesty-Humility are generally more risk-seeking. That is, they seem to be more willing to engage in risky behaviors, independent of how tempting or attractive the potential outcomes are.…”
Section: Resultsmentioning
confidence: 97%
“…Although personality is rather new to the Public Administration literature, core personality traits have been extensively used to explain differences in individual and group behavior across the social sciences. For example, de Vries and van Kampen (2010) use core personality traits to explain why certain individuals are more egoistic, pretentious or immoral, and Weller and Thulin (2012) and Weller and Tikir (2011) relate personality to risk-taking behavior. Furthermore, for instance, personality has been used by political scientists to explain voting behavior (e.g., Gerber et al, 2010), and general management scholars have explored the impact of personality in the context of a wide range of organizational processes and outcomes (e.g., Boone et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It measures risk-taking attitudes, the perception of risky situations and the expected benefits of risky situations. Weller and Tikir (2011) found correlations between DOSPERT and personality, as indexed by the HEXACO scale (Ashton & Lee, 2009). Their finding implies that personality could indirectly influence surrogate decision making.…”
Section: Risks Involved In Surrogate Decision Makingmentioning
confidence: 91%